The Chromosome-Level Genome of Miracle Fruit (Synsepalum dulcificum) Provides New Insights Into the Evolution and Function of Miraculin - Yang, Zhuang; Liu, Zhenhuan; Xu, Hang; Chen, Yayu; Du, Pengmeng; Li, Ping; Lai, Wenjie; Hu, Haiyan; Luo, Jie; Ding, Yuanhao (Frontiers in Plant Science, 2022)
Miracle fruit (Synsepalum dulcificum) is a rare valuable tropical plant famous for a miraculous sweetening glycoprotein, miraculin, which can modify sour flavours to sweet flavours tasted by humans. Here, we present a chromosome-level high-quality genome of S. dulcificum with an assembly genome size of ~550 Mb, contig N50 of ~14.14 Mb, and 37,911 annotated protein-coding genes. Phylogenetic analysis revealed that S. dulcificum was most closely related to C. sinensis and D. oleifera, and that S. dulcificum diverged from the Diospyros genus ~75.8 MYA, and that C. sinensis diverged from Synsepalum ~63.5 MYA. Ks assessment and collinearity analysis with S. dulcificum and other species suggested that a whole-genome duplication event (WGD) occurred in S. dulcificum and that there was good collinearity between S. dulcificum and V. vinifera. On the other hand, transcriptome and metabolism analysis with 6 tissues containing 3 developmental stages of fleshes and seeds of miracle fruit revealed that GO terms and metabolic pathways of ‘cellular response to chitin’, ‘plant-pathogen interaction’, and ‘plant hormone signal transduction’ were significantly enriched during fruit development. Interestingly, the expression of miraculin (Chr10G0299340) progressively increased from vegetative organs to reproductive organs and reached an incredible level in mature fruit flesh, with an FPKM (fragments per kilobase of transcript per million) value of ~113,515, which was the most highly expressed gene among all detected genes. Combining the unique signal peptide and the presence of the histidine-30 residue together composed the main potential factors impacting miraculin’s unique properties in S. dulcificum. Furthermore, integrated analysis of WGCNA, enrichment and metabolite correlation suggested that miraculin plays potential roles in regulating plant growth, seed germination and maturation, resisting pathogen infection and environmental pressure. In summary, valuable genomic, transcriptomic and metabolic resources provided in this study will promote the utilization of S. dulcificum and in-depth research on species in the Sapotaceae family.